Determinants of Fruits and Vegetables Consumption Behaviour in Student Elementary School of Pekanbaru City 2018 - Christine Vita Gloria Purba; Alhidayati Alhidayati; Riri Maharani; Lia Indriyani Hutabarat (Jurnal Dunia Gizi, 2019)
Background; Based on the results of the 2013 Ministry of Health's Basic Health Research in children aged 10 years and above who consumed less fruit and vegetables with a yield of 93.5%. Less fruits and vegetables consumption will inhibit the growth and development of children and increase the risk of disease. Objectives; To determined the determination of fruit and vegetable consumption in students of Elementary School 130 Pekanbaru City in 2018. Material and Method; type of research used analytic survey used cross sectional study. This research was carried out in Elementary School 130 Pekanbaru City. The sample of this study was students of class v and vi in Elementary School 130 Pekanbaru City who were taken by exhaustic sampling with a total of 113 samples. Results; there was a relationship between pleasure with a P value = 0,000 and POR = 9,200 (CI = 2,756-32,853), the role of parents in relation to vegetables with P value = 0.02 and POR = 4.163 (CI = 1.590-10,898), menu variation with P value = 0.003 and POR = 4.218 (CI = 1.549-11,485) with the help of fruit and vegetable consumption. There was no relationship between knowledge with P value = 0.792 and POR = 807 (CI = 340-1199), peer support with P value = 0.410 and POR = 1.479 (CI = 581-3,761). Conclusion; For mothers to pay attention to the intake of fruit and vegetables for children, be more creative to process food for children.